Socioeconomic ‘Distressed Communities Index’ Predicts Risk-Adjusted Mortality After Cardiac Surgery - Charles, Eric J. (Ann Thorac Surg, 2019)
BACKGROUND: The effects of socioeconomic factors other than insurance status and race on outcomes following cardiac surgery are not well understood. We hypothesized that the Distressed Communities Index (DCI), a comprehensive socioeconomic ranking by zip code, would predict operative mortality following coronary artery bypass grafting (CABG). METHODS: All patients who underwent isolated CABG (2010–2017) in the Virginia Cardiac Services Quality Initiative database were analyzed. The DCI accounts for unemployment, education level, poverty rate, median income, business growth, and housing vacancies, with scores ranging from 0 (no distress) to 100 (severe distress). Patients were stratified by DCI quartiles (I: 0–24.9, II: 25–49.9, III: 50–74.9, IV: 75–100) and compared. Hierarchical linear regression modeled the association between DCI and mortality. RESULTS: A total of 19,756 CABG patients were analyzed, with mean PROM of 2.0±3.5%. Higher DCI scores were associated with increasing PROM. Overall operative mortality was 2.1% [n=424] and increased with increasing DCI quartile (I: 1.6% [95], II: 2.1% [77], III: 2.4% [114], IV: 2.6% [138], p=0.0009). The observed-to-expected ratio for mortality increased as level of socioeconomic distress increased. After risk adjustment for STS predicted risk of mortality, year of surgery, and hospital, the DCI remained predictive of operative mortality after CABG (OR 1.14 for each 25-point increase in DCI, 95% confidence interval 1.04–1.26, p=0.007). CONCLUSIONS: The Distressed Communities Index independently predicts risk-adjusted operative mortality following CABG. Socioeconomic status, although not part of traditional risk calculators, should be considered when building risk models, evaluating resource utilization, and comparing hospitals.